2014
DOI: 10.1080/01292986.2014.944925
|View full text |Cite
|
Sign up to set email alerts
|

Chinese-style pragmatic objectivity in war reporting

Abstract: China plays an increasing role in the wars and conflicts around the world with its expanding political and economic interests overseas, and its diplomatic role in international affairs. More and more Chinese journalists go to the frontlines overseas to cover distant conflicts for domestic audiences. Based on semi-structured in-depth interviews with sixteen Chinese correspondents who have covered conflicts outside China, this study examines Chinese journalists' perceptions and reflections on objectivity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Yet Chinese journalists do not seem to fetishize truth to the same extent as their US and UK counterparts did in the previous study (Hearns-Branaman, 2014). This finding is similar to Zhang, who found that Chinese journalists ‘point out the limitations of objectivity and they think objectivity is an unattainable norm in practice’ (Zhang, 2014: 9).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Yet Chinese journalists do not seem to fetishize truth to the same extent as their US and UK counterparts did in the previous study (Hearns-Branaman, 2014). This finding is similar to Zhang, who found that Chinese journalists ‘point out the limitations of objectivity and they think objectivity is an unattainable norm in practice’ (Zhang, 2014: 9).…”
Section: Resultssupporting
confidence: 86%
“…As this is broadly the same as most criticisms of the limits US and UK news media, just in the specific political-economic context of the PRC, I argue that it deserves some direct comparison with discourses of the Anglo-American system. Furthermore, other studies have argued that ‘Objectivity and balance have become main news values and ideologies to Chinese journalists’ (Zhang, 2014: 2), and it remains to test this notion further. Lin (2010) argues that mainland Chinese journalism contains elements of Western-style professionalism along with party journalism and the Chinese literati tradition, in that Western professionalism has been localized and a transition towards complete Western professionalism is not inevitable.…”
Section: Other Professionalism Contextsmentioning
confidence: 99%
“…To be objective is thus a journalistic strategy by which journalists can interpret reality but avoid post-publication retribution from the political authorities, especially when these opinions are not in line with the economic priority of the CCP and may even have the potential to impair the economic interests of its allies. This strategy and the purposes and the consequences of using this strategy however are different from those analyzed in Tuchman’s and Gitlin’s work (Gitlin, 1980; Tuchman, 1972) and from that in Zhang’s research (Zhang, 2014). In this study, objectivity is adopted by journalists to express (their own) opinions without inviting political punishment.…”
Section: Discussionmentioning
confidence: 78%
“…While journalists’ acceptance of objectivity provides some evidence of the influence of American journalistic norms on Chinese journalism, both what objectivity means to Chinese journalists and how this notion guides their practices remain unclear. Very recently, Zhang (2014) examined how 16 Chinese war correspondents who have covered conflicts outside China perceive objectivity and argues that objectivity is used as a “practical ritual” by these journalists to facilitate their work in foreign war zones and even to promote “allegiance and patriotism.” This interesting case however is limited by the focus on war correspondents who do their work in foreign territories. Nor did this study touch on whether the journalists actually do their job according to their understanding of objectivity.…”
Section: Journalism In Chinamentioning
confidence: 99%
“…The pragmatists. Knowing that the ideal of complete objectivity can never be achieved, they propose that the pursuit of it defines good journalistic craftsmanship (Bentele, 2008;Carpentier and Trioen, 2010;Tuchman, 1972;Ward, 2005;Zhang, 2014). Ward (2005), who established the term "Pragmatic Objectivity", considers it "a holistic, fallible, rational evaluation of reports" (Ward, 2005, 300).…”
Section: Hypothesis and Objectivesmentioning
confidence: 99%